Criteria of adequacy of mathematical domain model - Малахов, Евгений Валериевич; Востров, Георгий Николаевич (Eastern-European Journal of Enterprise Technologies, 2010)
The occurrence probabilities in problem domains of entities describing by random variables and processes, the nominal or mixed attributes were considered. The criteria of adequacy of domain models, depending on the objects attributes belonging to the respective classes were suggested.